Development of a Computer Based Energy Management System - Nagle, Liam (Cranfield University, 1998)
A prototype computer based expert system has been developed to aid energy managers by speeding the energy auditing process and rapidly identifying potential low cost and fast pay-back energy saving investments for a wide range of businesses. It consists of a generally applicable energy management system based on sound, tried theory and practical experience gained from a number of energy management surveys. These surveys were used to identify key data requirements for the identification of common areas of wastage. The system uses sparse data analysis and the building energy signature model. It produces an entire energy audit and list of economic recommendations for a site based upon minimal input data. This is accomplished by reference to a number of internal databases containing the technical information required, as well as the entire set of algorithms and mathematical routines required for the analyses. The prototype was tested with a synthetic data set derived from the site surveys and with real data from a large tertiary college and it was found to give credible results in line with those produced by extensive and in-depth manual data-gathering and analysis.